A tripodal supramolecular sensor to successively detect picric acid and CN− through guest competitive controlled AIE. (10th January 2019) - Lin, Qi; Guan, Xiao-Wen; Fan, Yan-Qing; Wang, Jiao; Liu, Lu; Liu, Juan; Yao, Hong; Zhang, You-Ming; Wei, Tai-Bao
Abstract : Herein, we report a simple and efficient method for the selective and sensitive detection of picric acid (PA ) and CN − via a novel guest competitive controlled aggregation-induced emission (AIE) mechanism based on a tris-naphthalimide derivativeTG . Abstract : Efficient detection of explosives ( e.g. picric acid) and toxic compounds ( e.g. cyanide) is an important task. Herein, we report a simple and efficient method for the selective and sensitive detection of picric acid (PA ) and CN − via a novel guest competitive controlled aggregation-induced emission (AIE) method. First, a tripodal host compound (TG ) based on a tris-naphthalimide derivative was designed and synthesized. TheTG can self-assemble to a supramolecular system and show blue AIE. Then, we employed theTG -based supramolecular system as a novel supramolecular sensor (S-TG ). Interestingly, S-TG could selectively detectPA through a competitive binding interaction, and the detection limit (LOD) ofS-TG forPA is 1.19 × 10 −8 M. In this process, the self-assembly ofS-TG was destroyed and aTG andPA complex (TG–PA ) was produced, meanwhile, the AIE ofS-TG was quenched. More interestingly, TG–PA could act as a novel supramolecular sensor for the AIE fluorescent 'turn-on' detection of CN −, and the LOD ofTG–PA for CN − is 7.45 × 10 −7 M. Moreover, PA and CN − test kits were prepared by loadingS-TG orTG–PA on silica gel plates. These test kits could conveniently and efficiently detectPA or CN − with high selectivity and sensitivity.